2016
DOI: 10.3390/s16050701
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Probe’s Morphology for Metal Ion Detection Based on Light-Addressable Potentiometric Sensors

Abstract: The sensing mechanism of binding Hg2+ into thymine-thymine (T-T) mismatched base pairs was introduced into a light-addressable potentiometric sensor (LAPS) with anti-Hg2+ aptamer as the sensing units. Three kinds of T-rich single-strand DNA (ssDNA) chains with different spacer lengths, from 0 to 12 –CH2 groups, were designed to investigate surface charge and morphological effects on the LAPS’ output. First, by comparing the responding of LAPS modified with three kinds of ssDNA, it was found that the best perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…It is indicated that V out is enhanced by the increased V RE . Though qualitative explanation has been provided for this observation, , we still want to have an intrinsic view in LAPS, so that a clear computable LAPS principle could be formed, it will promote LAPS developing in a broader discipline. This work has not been reported up-to-now and will be accomplished here, for the first time.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is indicated that V out is enhanced by the increased V RE . Though qualitative explanation has been provided for this observation, , we still want to have an intrinsic view in LAPS, so that a clear computable LAPS principle could be formed, it will promote LAPS developing in a broader discipline. This work has not been reported up-to-now and will be accomplished here, for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…However, to the best of our knowledge, only three reports are found, they belong to two of three FNA sensors 18 and named as (1) genoLAPS, which is modified by single strand DNA (ssDNA) to monitor DNA hybridization; 28−30 (2) aptaLAPS, which is modified by aptamer to realize Hg + detection. 31 The work for DNAzyme type LAPS (DNAzyme-LAPS) is missing. Moreover, in-depth understanding for the intrinsic mechanisms of FNA-LAPS experimental results are still in necessary, since the current surface charge (SC) sensing mechanisms 28−31 cannot explain why LAPS output signals (V out or I out ) can respond to the erecting FNAs reaction, 31 and our measured changing of V out (ΔV out) caused by long FNAs is smaller than short ones.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Hg 2+ was detected with an aptamer-modified LAPS. The surface potential was influenced by the aptamer's morphology and charge [116]. A carboxylated graphene oxide (GO-COOH)-modified LAPS substrate was developed for the label-free detection of circulating tumour cells by measuring potential shifts [117].…”
Section: (Vi) Extracellular Potentials and Ionic Currentsmentioning
confidence: 99%